Edukasi Dampak Pestisida dan Pemeriksaan Kandungan Pestisida pada Sumber Air Minum Petani di Desa Borisallo, Kec. Parangloe, Kab. Gowa - Abdul Gafur; Sri Julyani; Ulfa Sulaeman (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
Pesticides are used to control pests in farming and plantations, so that agricultural and plantation production can increase. However, the use of pesticides can have a negative impact on the environment and the health of farmers. In fact, it causes poisoning and disease, both acutely and chronically. Farmers are the main work that the community is engaged in in Borisallo Village, Parangloe District, Gowa Regency and is a PKM partner and is a UMI Assisted Village. PKM activities are: (1) Counseling on negative impacts on health due to the use of pesticides, (2) Sanitary inspections and inspection of pesticide content in clean water sources such as wells, (3) Provision of PPE in the form of masks and gloves in spraying pesticides on farmers in Borisallo Village. This activity is funded by the UMI Waqf Foundation. The results of the implementation of PKM (1) Health counseling due to the use of pesticides on farmers in Borisallo Village, (2) Then continued with sanitary inspections and examination of pesticide content in clean water sources such as wells (3) Ended with the provision of PPE in the form of masks and gloves that can be used when spraying pesticides on farmers. It is recommended to have regular health checks on farmers, regular inspections of clean water sources, and technical guidance on how to manage and spray pesticides safely and healthily.